2021
DOI: 10.3390/insects13010043
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Alpine Butterfly Communities during the Last 40 Years

Abstract: Our work aims to assess how butterfly communities in the Italian Maritime Alps changed over the past 40 years, in parallel with altitudinal shifts occurring in plant communities. In 2019, we sampled butterflies at 7 grassland sites, between 1300–1900 m, previously investigated in 2009 and 1978, by semi-quantitative linear transects. Fine-scale temperature and precipitation data elaborated by optimal interpolation techniques were used to quantify climate changes. The changes in the vegetation cover and main hab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
12
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 99 publications
3
12
1
Order By: Relevance
“…Moreover, butterflies tend to react quickly to environmental changes by virtue of biological features such as their complex demands during life cycle, their mobility and short lifespan (van Swaay et al 2010;Bonelli et al 2018). Different consequences of climate change have been documented for mountain butterflies, including distribution shifts towards higher altitudes (Forister et al 2010;Rödder et al 2021) and an overall expansion of thermophilous and generalist species, in parallel to a decrease of more specialised ones (Zografou et al 2014;Cerrato et al 2019;Macgregor et al 2019;Bonelli et al 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, butterflies tend to react quickly to environmental changes by virtue of biological features such as their complex demands during life cycle, their mobility and short lifespan (van Swaay et al 2010;Bonelli et al 2018). Different consequences of climate change have been documented for mountain butterflies, including distribution shifts towards higher altitudes (Forister et al 2010;Rödder et al 2021) and an overall expansion of thermophilous and generalist species, in parallel to a decrease of more specialised ones (Zografou et al 2014;Cerrato et al 2019;Macgregor et al 2019;Bonelli et al 2022).…”
Section: Introductionmentioning
confidence: 99%
“…First, agricultural intensification and extensive modification of land use accelerated since the 1950s (SW‐Germany) and 1960s (C‐Austria) and represent an ongoing trigger of faunal change (Jepsen et al, 2015). Second, climate change started to affect butterfly species abundances and assemblage structures since the 1980s (Habel et al, 2022), but did not measurably affect diversity so far (Bonelli et al, 2021; Habel et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Prior work on these SW‐German and C‐Austrian butterflies (Habel et al, 2019, 2022) identified major breakpoints in butterfly relative abundances in the 1960s. These changes were manifest in decreasing proportions of lowland species associated with oligotrophic and xerothermophilic habitats, for example, for most burnet moths and many blues, as well as an uphill shift of species ranges due to climate change, for example, for many Erebia species (Bonelli et al, 2021; Habel, Ulrich, et al, 2023; Rödder et al, 2021). In the present case, we argue that agricultural intensification and other land use changes, mostly occurring simultaneously in both study regions, were the main drivers for the observed trends in assemblage composition as these coincide in time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of studies have reported data on the global effects of climate change on arthropods from cold environments at the population and community levels (Bonelli et al, 2022; Chown & Brooks, 2019). However, the responses of polar (Arctic, sub‐Antarctic, Antarctic) ectothermic species to current and future environmental variability, stochastic environmental fluctuations, or extreme events are rarely addressed and thus remain under‐represented in the literature (Bahrndorff et al, 2021; Høye, 2020; but see a range of experimental environmental manipulation studies, as reviewed by Bokhorst et al, 2013).…”
Section: Introductionmentioning
confidence: 99%